Association between glycolipids and risk of obstructive sleep apnea: A population-based study - Zheng, Murui; Duan, Xueru; Zhou, Huanning; Sun, Weidi; Sun, Guoqiang; Chen, Jianying; Wu, Xiuyi; Rong, Sijing; Huang, Jun; Zhao, Wengjing; Deng, Hai; Liu, Xudong (Frontiers in Nutrition, 2023)
Background: This study aimed to investigate the associations between glycolipid biomarkers and the risk of obstructive sleep apnea (OSA). Methods: 10,286 participants aged from 35 to 74 years old were included in this cross-sectional study from the baseline survey of the Guangzhou Heart Study. OSA risk was ascertained using both Berlin Questionnaire (BQ) and STOP-BANG Questionnaire (SBQ). Participants who were assessed as having a high risk of OSA by both BQ and SBQ were classified into the OSA group, those who were assessed as having a lower risk of OSA by both BQ and SBQ were classified into the non-OSA group, and the remaining participants were classified in the pre-OSA group. Fasting blood samples were collected from each participant; fasting blood glucose (FBG) and serum concentrations of high-density lipoprotein cholesterol (HDL-CH), low-density lipoprotein cholesterol (LDL-CH), total cholesterol (TC)，and triglyceride (TG) were determined. Odds ratio (OR) with 95% confidence interval (CI) was calculated using the multivariate logistic regression model after adjustment for covariates. Results: Of the participants included, 15.56% were categorized into the pre-OSA group, and 8.22% into the OSA group. When comparing the highest with the lowest quartiles, HDL-HC was associated with a 22% (OR: 0.78, 95% CI: 0.65 - 0.94) and 41% (OR: 0.59, 95% CI: 0.45 - 0.78) reduced risk of pre-OSA and OSA, triglyceride was associated with a 32% (OR 1.32, 95% CI 1.08–1.60) and a 56% (OR 1.56, 95% CI 1.18–2.07) increased risk of pre-OSA and OSA, and FBG was associated with a 1.37-fold (95% CI 1.13–1.67) risk of pre-OSA and 1.38-fold (95% CI 1.03–1.85) risk of OSA after adjustment for potential confounders. A significant exposure-response trend was observed for HDL-HC, TG, and FBG with both OSA and pre-OSA (all P <0.05). No significant association of LDL-CH and TC with the risk of both pre-OSA and OSA was observed. Conclusions: The findings suggest that serum HDL-CH, TG and FBG were associated with OSA risk. Healthy glycolipid metabolism warrants more attention in the reduction of OSA risk.